A Roman fortlet and medieval lowland castle in the Upper Rhine Graben (Germany): archaeological and geoarchaeological research on the Zullestein site and the fluvioscape of Lorsch Abbey - Prien, Roland; Appel, Elena; Becker, Thomas; Bubenzer, Olaf; Fischer, Peter; Mächtle, Bertil; Willershäuser, Timo; Vött, Andreas (Heritage, 2025)
This study examines the Roman burgus and medieval lowland castle ‘Zullestein’ near Biblis (Bergstraße district/Hessen/Germany) and its surrounding fluvio-scape. The aim of the study is to reassess the appearance of the fortifications and the surrounding area at the confluence of the River Weschnitz and the River Rhine based on the excavation results from the 1970s and current geoarchaeological research on site. Our approach encompasses electrical resistivity tomography, direct push sensing, sediment coring and the use of a high-resolution digital elevation model in combination with historical depictions of the Zullestein site from the 17th century AD. The findings of this integrative approach indicate that the Roman fort was likely located at a secondary channel of the River Rhine. With the renewed occupation of the Zullestein site by Lorsch Abbey during Carolingian times and the expansion into a lowland castle in the 11th century, the site was now located at the Weschnitz mouth into the Rhine, likely as part of anthropogenic interventions related to the Weschnitz fluvioscape. Traces of the final phase of the castle at the time of the Thirty Years’ War can still be seen in the terrain today and their attribution to individual elements of the historical account can be confirmed by the geoarchaeological results. The combination of methods presented in this study is a suitable option if excavations are not possible.